A new global health alert caused by monkeypox - Gomez de la Rosa, Richar Jose; Rojas Hernandez, Juan Pablo (Interdisciplinary Journal of Epidemiology and Public Health, 2022)
Introduction: Monkeypox is a zoonosis of viral etiology caused by the Monkeypox virus, it is an endemic disease in African countries. Outside this area, the first cases were reported in 2003 in the USA. In May 2022, the World Health Organization (WHO) warned about the increase in the number of cases of monkeypox in non-endemic areas such as countries of Europe and North America, setting off international alarms in the face of the spread of the disease. Objective: To review the literature on monkeypox with special emphasis on virological and epidemiological aspects, transmission mechanism, clinical manifestations, and treatment expectations. Methods: A review of articles in Spanish and English using terms such as monkeypox, monkeypox, and monkeypox. Using search engines like PubMed, Medline, and ScienceDirect. It was complemented with web pages of recognized institutions because it was necessary to monitor the new cases that are registered worldwide and that are not published due to the speed of appearance and the short period of time. Results: The epidemiology, etiology, clinical manifestations, complications, isolation, and treatment possibilities of monkeypox. Conclusions: Monkeypox is an inexact substitute for variola virus smallpox. Early clinical features of the disease and patients not vaccinated against the variola virus are factors associated with poor outcomes. Management strategies and protective measures are key to preventing the spread of the disease.